Development of Quality Information Management System for Alumina Ceramic Tube Manufacturing Process - Yulong Huang (Advances in Materials Science and Engineering)
This paper is based on the alumina ceramic manufacturing process and its quality to build a quality information management system to study alumina ceramics and its quality factors such as physical properties, chemical properties, and other pieces of related information to find a kind of alumina ceramics. The management of quality management brings efficiency and guarantee to the management system. Obviously, this research is based on the two parts of alumina ceramic tube and quality management information system for data acquisition and analysis. One part is based on the production and performance analysis of alumina ceramic tube and summarizes the quality problems that occurred in this process. This paper constructs an information management system to count these issues and conducts research on information dominance and management; among them, exponential smoothing calculation methods, linear trends, convolutional neural algorithms, and so on are applied for methodological analysis. The experimental results show that the lack of corners and uneven corners in alumina production has been greatly reduced, and the maximum probability of uneven corners has been reduced from 9.27 to 5.27. The scrap rate of ceramic tube quality decreased from the highest value of 5.82 to 3.17, and the maximum value of unqualified quality was changed from 5.76 to 3.03.